A Comparison of Methods to Identify the Mean Response Time of Ramp-Incremental Exercise for Exercise Prescription - Behboodpour, Nikan; Halvorson, Brayden; Murias, Juan M.; Keir, Daniel; Belfry, Glen (Research quarterly for exercise and sport, 2024)
Introduction: The oxygen uptake ( ${{\dot {\rm{V}}}$ V ˙ O 2 ) vs power output relationship from ramp incremental exercise is used to prescribe aerobic exercise. As power output increases, there is a delay in ${{\dot {\rm{V}}}$ V ˙ O 2 that contributes to a misalignment of ${{\dot {\rm{V}}}$ V ˙ O 2 from power output; the mean response time (MRT). If the MRT is not considered in exercise prescription, ramp incremental-identified power outputs will elicit ${{\dot {\rm{V}}}$ V ˙ O 2 values that are higher than intended. We compared three methods of determining MRT (exponential modeling (MRT EXP ), linear modeling (MRT LIN ), and the steady-state method (MRT SS )) and evaluated their accuracy at predicting the ${{\dot {\rm{V}}}$ V ˙ O 2 associated with power outputs approximating 75% and 85% of gas exchange threshold and 15% of the difference between gas exchange threshold and maximal ${{\dot {\rm{V}}}$ V ˙ O 2 (Δ15). Methods: Ten males performed a 30-W∙min −1 ramp incremental and three 30-min constant power output cycle ergometer trials with intensities at 75% gas exchange threshold, 85% gas exchange threshold, and ∆15. At each intensity, the measured steady-state ${{\dot {\rm{V}}}$ V ˙ O 2 during each 30-min test was compared to the ${{\dot {\rm{V}}}$ V ˙ O 2 predicted after adjustment by each of the three MRTs. Results: For all three MRT methods, predicted ${{\dot {\rm{V}}}$ V ˙ O 2 was not different (p = 1.000) from the measured ${{\dot {\rm{V}}}$ V ˙ O 2 at 75%GET (MRT EXP , 31 mL, MRT LIN , −35 mL, MRT SS 11 mL), 85%gas exchange threshold (MRT EXP −14 mL, MRT LIN −80 mL, MRT SS −32 mL). At Δ15, predicted ${{\dot {\rm{V}}}$ V ˙ O 2 based on MRT EXP was not different (p = .767) from the measured ${{\dot {\rm{V}}}$ V ˙ O 2 , but was different for MRT LIN (p < .001) and MRT SS (p = .03). Conclusion: Given that the intensity is below gas exchange threshold, all model predictions implemented from the current study matched the exercise prescription.